LA NOUVELLE DYNAMIQUE FONCIERE AUTOUR DES EMPRISES DES LIGNES ELECTRIQUES DE HAUTE TENSION DANS LA COMMUNE DE YOPOUGON (CÔTE D’IVOIRE) - Valentin, KRA Kouakou (European Scientific Journal, ESJ, 2015)
The urban land question is one of the essential problems with which the public authorities and the populations in the African cities are confronted. In the Commune of Yopougon to Abidjan, the influences of the electric lines of high voltage are the object of a new land dynamics through the emergence of many actors in the illegal and anarchistic occupation of these spaces. At the origin, one evokes the fight against the insecurity on these grounds left in waste land as well as socio-economic determinants and infrastructurels. In spite of their dangerousness, these influences become true slums, markets and workshops as well as places of worship. Exit of the process of decentralisation, this situation is exacerbated because of the passivity and the populism of the public authorities, of the flexibility of the regulation framework and the antisocial behaviour of the populations. The formal and rational management of land urban by the State gives way to an abstract management or a privatization of the public domain by the municipality, certain agents of the land administration as well as the populations. Under these conditions, worsens the living environment of these populations already vulnerabilized by the failure of the public policies, the negligence and by an urban development evil managed and prone to corruption.